(untitled) (Filološke pripombe, 2019)
After the big migration of the Shepherds from Spain and Portugal and their settlement on the Balkan Peninsula, they brought with them their language. In time, this language had become the basic language of all Macedonian Jews. That is Hebrew – Spanish language, or so called “ladino”. The Hebrew – Spanish language is a speech of all Sephardic Jews in the world and presents a unique phenomenon in linguistic history. That is a language of the Spain’s 15th century, which survived among the Shepherds for 500 years, remaining the same as it was in that time. During the Ottoman rule, the Macedonian Jews created and cherished one’s own authentic folklore. It was consisted from folk stories, songs, proverbs, jokes, which have been remembered from generation to generation.